Juan Gregorio Palechor : The Story of My Life - Jimeno, Myriam (Book collections on Project MUSE., 2014)
The Colombian activist Juan Gregorio Palechor (1923-1992) dedicated his life to championing indigenous rights in Cauca, a department in the southwest of Colombia, where he helped found the Regional Indigenous Council of Cauca. Recounting his life story in collaboration with the Colombian anthropologist Myriam Jimeno, Palechor traces his political awakening, his experiences in national politics, the disillusionment that resulted, and his turn to a more radical activism aimed at confronting ethnic discrimination and fighting for indigenous territorial and political sovereignty.